LINGUISTIC FEATURES OF EUPHEMISMS IN ENGLISH AND UZBEK LANGUAGES - No’monova Zebinso Usmonjon qizi (Bright Mind Publishing, 2025)
The article discusses the discursive characteristics of euphemisms, their role in comparative languages, their study, and general classification. It also focuses on linguists’ scientific and theoretical perspectives on euphemisms, summarizing their distinctive features.
Keywords: Language, speech, thinking, euphemism, euphemism, efema, discourse, taboo, linguistic culture, pragmatics, system, norm, metaphor, metonymy, synecdoche, proverb, saying.